Development of College Student Analytical Thinking Skills Through Evaluation Learning with Flip Book Assisted E-Books - Susiaty, Utin Desy; Oktaviana, Dwi; Firdaus, Muhamad (Kreano, Jurnal Matematika Kreatif-Inovatif, 2022)
The purpose of this study was to compare college student analytical thinking skills in evaluation learning with and without flipbook-assisted e-books. The research method used is quasi-experimental with a nonequivalent control group research form. The sample in this study were fourth-semester college students. The result of the research is that the college student analytical thinking ability after being given a mathematics learning evaluation course with and without an e-book assisted by a flipbook is equally good. This study carries out the application of learning mathematics learning evaluation courses with e-books assisted by flipbooks as an effort to develop students' analytical thinking skills which are indispensable in solving problems in these subjects where so far no one has conducted research in this field. The implications of the research are by applying the learning of mathematics learning evaluation courses with e-books with the help of flipbooks to the maximum extent that they can develop college student analytical thinking skills.Tujuan dalam penelitian ini adalah untuk membandingkan kemampuan berpikir analitis mahasiswa dalam pembelajaran evaluasi dengan dan tanpa e-book berbantuan flipbook. Metode penelitian yang digunakan adalah quasi experimental dengan bentuk penelitian nonequivalent control group. Sampel dalam penelitian ini adalah mahasiswa semester IV. Hasil penelitian yaitu kemampuan berpikir analitis mahasiswa sesudah diberikan mata kuliah evaluasi pembelajaran matematika dengan dan tanpa e-book berbantuan flipbook sama baiknya. Penelitian ini mengusung penerapan pembelajaran mata kuliah evaluasi pembelajaran matematika dengan e-book berbantuan flipbook sebagai upaya dalam mengembangkan kemampuan berpikir analitis mahasiswa yang sangat diperlukan dalam menyelesaikan permasalahan di mata kuliah tersebut dimana selama ini belum ada yang melakukan penelitian di bidang tersebut. Adapun implikasi dalam penelitian yaitu dengan melakukan penerapan pembelajaran mata kuliah evaluasi pembelajaran matematika dengan e-book berbantuan flipbook secara maksimal dapat mengembangkan kemampuan berpikir analitis mahasiswa.